Natural Killer Cell Receptor Genes in Camels: Another Mammalian Model - Futas, Jan; Oppelt, Jan; Jelinek, April; Elbers, Jean P.; Wijacki, Jan; Knoll, Ales; Burger, Pamela A.; Horin, Petr (Frontiers in Genetics, 2019)
Due to production of special homodimeric heavy chain antibodies, somatic hypermutation of their T-cell receptor genes and unusually low diversity of their major histocompatibility complex genes, camels represent an important model for immunogenetic studies. Here, we analyzed genes encoding selected natural killer cell receptors with a special focus on genes encoding receptors for MHC class I ligands in the two domestic camel species, Camelus dromedarius and Camelus bactrianus. Based on the dromedary genome assembly CamDro2, we characterized the genetic contents, organization and variability of two complex genomic regions, the leukocyte receptor complex and the natural killer complex, along with the natural cytotoxicity receptor genes NCR1, NCR2 and NCR3. The genomic organization of the natural killer complex region of camels differs from cattle, the phylogenetically most closely related species. With its minimal set of KLR genes, it resembles this complex in the domestic pig. Similarly, the leukocyte receptor complex of camels is strikingly different from its cattle counterpart. With KIR pseudogenes and few LILR genes, it seems to be simpler than in the pig. The syntenies and protein sequences of the NCR1, NCR2 and NCR3 genes in the dromedary suggest that they could be human orthologues. However, only NCR1 and NCR2 have a structure of functional genes, while NCR3 appears to be a pseudogene. High sequence similarities between the two camel species as well as with the alpaca Vicugna pacos were observed. The polymorphism in all genes analyzed seems to be generally low, similar to the rest of the camel genomes. This first report on natural killer cell receptor genes in camelids adds new data to our understanding of specificities of the camel immune system and its functions, extends our genetic knowledge of the innate immune variation in dromedaries and Bactrian camels, and contributes to studies of natural killer cell receptors evolution in mammals.